The Influence of Work Stress and Physical Work Environment on Employee Performance Through Work Motivation Among Marketing Employees at Bank Syariah Indonesia Tapaktuan - Rosi Rauziqmi; Yeni Absah; Rahim Matondang (Journal of Business Management, 2025)
Employee performance is a crucial factor in achieving organizational goals. However, the performance of employees at PT. Bank Syariah Indonesia in the Tapaktuan region remains suboptimal, as evidenced by unmet work targets and low achievement of key performance indicators. Based on preliminary survey results, work stress, physical work environment, and work motivation were identified as dominant factors contributing to performance decline. This study aims to analyze the influence of work stress and physical work environment on employee performance, with work motivation as a mediating variable. A quantitative approach was employed, using questionnaires distributed to 52 marketing staff respondents. The preliminary survey revealed that most employees experienced stress due to high workloads and tight deadlines, worked in uncomfortable environments, and had low work motivation, both internally and externally. Work motivation was found to play a significant role in strengthening or weakening the influence of stress and work environment on performance. This study contributes to the development of human resource management theory and provides practical recommendations for management to improve performance through enhancing the work environment, managing stress, and increasing motivation. Future research is recommended to involve a larger sample size and to consider other variables such as leadership and organizational culture.